Everything you always wanted to know about curating but were afraid to ask - Obrist, Hans Ulrich, 1968- (Sternberg Press, 2011)
Interview s Hansem Ulrichem Obristem, kurátorem uměleckých výstav a uměleckým kritikem. Rozhovory o životě, práci a umění
Keywords: Obrist, Hans Ulrich, -- 1968-; kurátoři výstav; umění; názory a postoje; umělecké výstavy; exhibition curators; art; views and attitudes; art exhibitions; rozhovory; interviews